Assessing annual energy production using a combination of lidar and mast measurement campaigns - Mkhaitari, Rachid; Mir, Yamina; Zazoui, Mimoun (Institute of Advanced Engineering and Science, 2023)
The current study evaluates the wind potential at early stage of wind project using met mast and lidar. The wind data obtained from a met mast located away from the turbines can be hindered by obstacles, leading to limited coverage and height, it negatively impacting the project's performances. To address the above limitations, the study suggests implementing a secondary measurement approach utilizing Lidars in various locations to cover the full study area. This work assesses the two measurements campaign and compares the wind potential evaluated with data measured by met mast and lidars. The simulations of two wind data base are quantified referring to the main key performance indicators for a project of total capacity of 140MW. The results show significant improvement in gross and net production for all exceedance scenarios, with 2% increase on the P90, and an improvement in the annual capacity factor by 1.09%. The use of Lidar data referenced to a met mast leads to accurate and bankable data, with the advances of cost and logistics, Lidars helps in layout configuration and performance evaluation.